Becoming a group: Value convergence and emergent work group identities. (14th January 2013) - Meeussen, Loes; Delvaux, Ellen; Phalet, Karen
<x xml:space="preserve">Abstract</x> This study examines the process of group identity formation through social interaction in real‐life work groups, with a focus on achievement values as content of work group identities. Extending research on social identity formation, we examined the process of value convergence as group members negotiate common group goals. Specifically, we predicted that work group members would influence each other's achievement values and that value convergence over time would underlie emergent work group identities and work group performance. Using a fully cross‐lagged multilevel design with four repeated measures in 68 work groups, we find that group members' achievement values converge through mutual social influence. Moreover, multilevel polynomial regression analysis reveals that value convergence – rather than group members' initial value fit – longitudinally predicts work group identification and performance.